Identifikasi dan pencegahan kontaminasi pada kultur cair sistem perendaman sesaat Identification and prevention of contamination in liquid culture of temporary immersion system - Masna Maya SINTA; Imron RIYADI; . SUMARYONO (E-Journal Menara Perkebunan, 2014)
AbstractLiquid culture is commonly used to scale up in vitro culture production as well as to optimize the developmental phase of plant in vitro culture. One of the liquid cultures that has been used widely is temporary immersion system (TIS). The main problem of liquid culture is contamination. The use of antibiotics sometimes controls the contaminants less effectively and hinders the growth of plant culture. The purpose of this research was to determine sources of contaminant on whole sequence of TIS to identify and to prevent the emergence of the contaminants. Sampling method was applied to each section and stage of TIS culture and the contaminants found were identified. The results revealed that compartment of TIS was the main source of contaminant (100%). Furthermore, from all components of TIS compartment, washer (a small ring seal connecting screen disc and basket) was the main source of TIS contaminant (41.2%). Four contaminants found were identified as Bacillus macerans, Bacillus megaterium, Bacillus sphaericus and Bacillus firmus. Two times sterilization of washer in an autoclave at temperature of 121 oC and air pressure of 1 kg/cm2 for 20 minutes before and after being installed reduced the contamination level on TIS culture significantly.AbstrakKultur cair umumnya digunakan untuk meningkatkan skala produksi dan mengoptimalkan fase perkembangan kultur in vitro tanaman. Salah satu jenis kultur cair yang banyak digunakan adalah sistem perendaman sesaat (SPS). Masalah utama dalam kultur cair adalah kontaminasi. Penggunaan antibiotika terkadang kurang efektif dalam me-ngendalikan kontaminan dan menghambat pertumbuhan kultur tanaman. Tujuan dari penelitian ini adalah untuk mengetahui sumber kontaminan pada seluruh rangkaian kultur SPS serta mengidentifikasi dan mencegah munculnya kontaminan tersebut. Metode yang digunakan adalah  pengambilan contoh pada tiap bagian dan fase kultur SPS, serta kontaminan yang ditemukan kemudian diidentifikasi. Hasil penelitian memperlihatkan bahwa kompartemen SPS merupakan sumber utama kontaminan (100%). Selanjutnya, dari seluruh komponen kompartemen SPS, washer (cincin penutup yang menghubungkan penyaring dan keranjang) di dalam rangkaian SPS merupakan sumber utama kontaminan (41,2%).  Empat  kontaminan yang ditemukan diidentifikasi sebagai Bacillus macerans, Bacillus megaterium, Bacillus sphaericus dan Bacillus firmus. Sterilisasi cincin penutup sebanyak  dua  kali  dalam  autoklaf pada suhu 121 oC dan tekanan udara 1 kg/cm2selama 20 menit sebelum dan sesudah dirangkai secara nyata menurunkan tingkat konta-minasi pada kultur SPS.